Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada Saera Home Living - Nazwa Putri Gunawan; H.Asep Jamaludin; Zenita Apriani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to examine the partial and simultaneous effects of work motivation and work discipline on employee performance at Saera Home Living. This research employs a quantitative method with an associative approach, involving 53 employees selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression, including validity, reliability, classical assumption, and hypothesis testing. The results reveal that work motivation has a positive and significant effect on employee performance, indicating that motivational factors play a dominant role in improving employee outcomes. In contrast, work discipline does not have a significant partial effect, suggesting that formal compliance alone is insufficient to enhance performance without internal motivation. However, both variables simultaneously influence employee performance, with a contribution of 47%, while the remaining 53% is explained by other factors. This study contributes to the literature by highlighting a contextual finding where work discipline does not significantly affect performance in a project-based interior industry setting. It emphasizes that employee performance is more strongly driven by psychological factors rather than administrative control, offering both theoretical insight and practical implications for human resource management strategies.